2020
DOI: 10.1021/acs.jced.9b01042
|View full text |Cite
|
Sign up to set email alerts
|

P–ρ–T Data and Modeling for Butan-1-ol + n-Octane or n-Decane between 313.15–353.15 K and 0.1–20 MPa

Abstract: Density measurements conducted for the binary systems of butan-1-ol (1) + n-octane (2) and butan-1-ol (1) + n-decane (2) at high pressures are presented in this work. These measurements were conducted utilizing an Anton Paar DMA HP densitometer and encompass the entire composition range, with a temperature and pressure range of T = (313.15–353.15 K) and P = (0.1–20 MPa), respectively. The modified Toscani–Szwarc equation of state was employed to successfully correlate the experimental density data. The measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 77 publications
2
17
0
Order By: Relevance
“…In this work, the empirical modified Toscani–Szwarc equation of state (MTS EOS) proposed by Quevedo-Nolasco et al as a variation of the Toscani–Szwarc equation of state was used to correlate the experimental density data, as previous studies have shown its effectiveness in correlating alcohol–alkane high-pressure density data. , Tait-type (9 parameters) and BWRS EOS (11 parameters) density models were also considered initially. In the majority of cases, the improvement of fit by these models was not significant based on F -test calculations.…”
Section: Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…In this work, the empirical modified Toscani–Szwarc equation of state (MTS EOS) proposed by Quevedo-Nolasco et al as a variation of the Toscani–Szwarc equation of state was used to correlate the experimental density data, as previous studies have shown its effectiveness in correlating alcohol–alkane high-pressure density data. , Tait-type (9 parameters) and BWRS EOS (11 parameters) density models were also considered initially. In the majority of cases, the improvement of fit by these models was not significant based on F -test calculations.…”
Section: Theorymentioning
confidence: 99%
“…The apparatus used for the high-pressure density measurements was described in previous work by Moodley and co-workers , and is shown in Figure .…”
Section: Experimental Sectionmentioning
confidence: 99%
See 3 more Smart Citations